Vitamin E in the treatment of primary dysmenorrhoea - S., Vilvapriya; S., Vinodhini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The objective of this study is to determine the efficacy of Vitamin E in the treatment of primary dysmenorrhoea compared to the placebo. Methods: Sixty women, aged 17-25 years old who suffered from primary dysmenorrhoea, among 1000 Women attending the gynec OPD in Kilpauk Medical College. 30 women were given 200 units of vitamin E (each tablet twice daily) and 30 were given a placebo tablets (each tablet twice daily). The treatment began two days before the beginning of menstruation and continued through the first three days of bleeding. The severity of pain and duration of pain before and after the treatment was studied. Treatment in both groups was carried out in three consecutive menstrual periods. Results: As to the findings, the mean age of the participants was 22.6 years. There was a significant difference between the pre- and post-treatment periods in terms of pain severity (P=0.72 and P=0.002, respectively) and pain duration (P=0.514 and P=0.027, respectively) in Vitamin E group. There was a significant difference observed between the Vitamin E group and placebo group regarding the mean of pain severity and duration (P=0.002 and p=0.027 respectively). Conclusions: Vitamin E helps to relieve pain in primary dysmenorrhoea. As this is a relatively easier method for control of pain with lesser amount of side effects and as it is cost effective, it can be considered as a universal drug in the treatment of primary dysmenorrhoea.